Inovasi edukasi dengan media website dan flashcard tentang gizi seimbang pada anak usia 2 – 5 tahun - Djohar, Zohna; Anggraini, Ika Rizki (JOURNAL of Public Health Concerns, 2025)
Background: The health of children aged 2-5 years is crucial for their growth and development and immune system. One important indicator of a child's health is their nutritional status. In Indonesia, malnutrition remains a challenge, with the prevalence among children aged 2-5 years reaching 17.1% in 2022. If left untreated, it can increase the risk of stunted growth, cognitive decline, and susceptibility to disease. Purpose: To increase mothers' knowledge about the importance of balanced nutrition for children aged 2-5 years using a website and flashcards. Method: The educational activity was held on Wednesday, July 2, 2025, from 1:00 PM to 2:00 PM WIB in Sukoanyar Village, RW 04/RT 04. This activity used a case study design with a one-group pre-test and post-test technique. Lecture methods, website media, and flashcards were used. Respondents in this educational activity were two toddlers and their two mothers. Educational materials are presented to mothers through a website containing structured explanations, definitions, types, benefits, the four pillars of nutrition, messages, and factors influencing balanced nutrition. Toddlers are also provided with illustrated flashcards and simple text to facilitate understanding. Results: Balanced nutrition education using a website and flashcards successfully improved the knowledge of mothers and children aged 2–5 years. The website education for mothers resulted in pre-test scores of 30 for respondent 1 and 50 for respondent 2, followed by post-test scores of 90 for respondent 1 and 80 for respondent 2, and post-test scores of 90 for respondent 1 and 90 for respondent 2. Meanwhile, flashcard education for toddlers resulted in pre-test scores of 6 for respondent 1 and 7 for respondent 2, and post-test scores of 10 for respondent 1 and 12 for respondent 2. Conclusion: The website and flashcards proved effective in improving mothers' knowledge of balanced nutrition and the understanding of children aged two to five years. The intervention demonstrated not only significant improvements in scores but also post-intervention knowledge retention and increased child engagement in the learning process. Suggestion: Balanced nutrition education programs need to be implemented routinely and sustainably by expanding the number of participants and involving health cadres and village officials to strengthen local support and validate findings. These programs should be accompanied by regular evaluations to monitor knowledge retention and adapt materials. They should also include the development of interactive content such as video tutorials and online quizzes to enrich learning methods and increase participant interest. Keywords: Early childhood; Flashcards; Nutrition education; Website media Pendahuluan: Kesehatan anak pada usia 2-5 tahun sangat menentukan proses tumbuh kembang dan daya tahan tubuh, salah satu indikator penting kesehatan anak ialah status gizinya. Di Indonesia, masalah gizi kurang masih menjadi tantangan dengan prevalensi pada anak usia 2-5 tahun mencapai 17.1% pada tahun 2022, jika tidak ditangani dapat menimbulkan risiko anak mengalami gangguan pertumbuhan, penurunan kemampuan kognitif dan mudah terserang penyakit.  Tujuan: Meningkatkan pengetahuan ibu tentang pentingnya gizi seimbang pada anak usia 2–5 tahun dengan menggunakan media website dan flashcard. Metode: Kegiatan edukasi dilaksanakan pada hari rabu, 02 juli 2025 pada pukul 13.00-14.00 WIB berlokasi di Desa Sukoanyar RW 04/RT 04. Kegiatan ini merupakan edukasi dengan desain penelitian case study dengan teknik one group pre-test dan post-test. Menggunakan metode ceramah, media website dan juga flashcard. Responden dalam edukasi ini adalah 2 balita dan 2 ibunya. Materi edukasi disajikan kepada ibu melalui situs web yang memuat penjelasan terstruktur, penyampaian definisi, jenis, manfaat, prinsip empat pilar, pesan, dan faktor yang memengaruhi gizi seimbang. Penjelasan kepada balita dengan media flashcard bergambar berteks sederhana untuk memudahkan pemahaman. Hasil: Edukasi gizi seimbang dengan media website, dan flashcard berhasil meningkatkan pengetahuan ibu dan anak usia 2–5 tahun. Menunjukkan bahwa edukasi dengan menggunakan website pada ibu mendapatkan skor pre-test responden 1 adalah 30 dan responden 2 adalah 50, selanjutnya untuk skor post-test1 responden 1 adalah 90 dan responden 2 adalah 80, kemudian untuk skor post-test2 responden 1 adalah 90 dan responden 2 adalah 90. Sedangkan untuk edukasi dengan menggunakan flashcard pada balita mendapatkan poin pre-test responden 1 adalah 6 dan responden 2 adalah 7, selanjutnya untuk poin post-test responden 1 adalah 10 dan responden 2 adalah 12. Simpulan: Media website dan flashcard terbukti efektif meningkatkan pengetahuan ibu mengenai gizi seimbang serta pemahaman anak usia dua hingga lima tahun. Intervensi menunjukkan tidak hanya peningkatan skor yang signifikan, tetapi juga retensi pengetahuan pasca intervensi dan peningkatan keterlibatan anak dalam proses pembelajaran. Saran: Program edukasi gizi seimbang perlu dilaksanakan secara rutin dan berkelanjutan dengan memperluas jumlah peserta serta melibatkan kader kesehatan dan perangkat desa untuk memperkuat dukungan lokal dan memvalidasi temuan, disertai evaluasi berkala guna memantau retensi pengetahuan sekaligus menyesuaikan materi, serta pengembangan konten interaktif seperti video tutorial dan kuis online untuk memperkaya metode pembelajaran dan meningkatkan minat peserta.